Association of demographic characteristics to depression, anxiety, and stress among diabetics: A cross-sectional report from resource-limited settings of South India - Vigneshwaran Easwaran; Sai Varun Kudumula Mulammagari; Chaitanyakumar Lakkepogu; Rajarajeshwari Byram; Sultan Mohammed Alshahrani; Sirajudeen Shaik Alavudeen; Noohu Abdulla Khan (Wolters Kluwer Medknow Publications, 2021)
Background: In India, there is a scarcity of epidemiological data related to risk factors and prevalence of depression, anxiety, and stress (DAS) among diabetics. Therefore, their estimation may provide data for an effective management of these disorders in diabetic patients. Aim: The current study was undertaken to analyze the effect of sociodemographic characteristics toward DAS symptoms and to estimate the prevalence of DAS among diabetics. Materials and Methods: It was a cross-sectional study conducted among diabetics at the resource-limited settings of South India. Non probabilistic convenient sampling was used for recruitment fo study subjects. DAS scale 21 questionnaire is a validated self-report questionnaire designed to measure the severity of a range of symptoms for DAS. The patients with established psychiatric disorders were excluded from the study. Results: Overall, the prevalence of DAS symptoms was 57.5%, 55.9%, and 44.9%, respectively, and which ranges from mild to extremely severe. Gender plays a major role in increasing the prevalence of depressive and stress symptoms. The elderly age group was found to have more prevalence of all these three symptoms than younger age. Conclusions: The study showed that the prevalence of DAS symptoms was high. However, in our study, these symptoms are poorly associated to demographic characteristics. We recommend to screen all the diabetic patients for DAS symptoms.